Analisis Sistem Informasi Akuntansi Penjualan Dan Pembelian Bahan Baku Pt Sagitarius - Aceu Ardiansyah; Adam Karim Nurdiansyah; Ester Christianty; Febi Febriani; Muhamad Fadli Nur Insan; Elok Faiqoh Himmah (LPPM Universitas Informatika dan Bisnis Indonesia, 2022)
Companies are the forerunner of economic activity. The development of the times makes every company must be more innovative and creative, one of which is in the use of technology. The accounting information system is the main foundation in every business process in order to present information on the company's financial statements. The company makes sales as the company's main goal in seeking profit. Sales is one of the company's business operations which is the core and becomes crucial information for the owners of the company's capital. PT Sagittarius is a company engaged in property and real estate that provides housing development services and is sold either in cash or on credit. Sales on credit are made through the bank, so PT Sagittarius will still receive cash from the bank that has been selected as the lender. In this case, there are several internal control systems on sales that need to be re-analyzed and provide recommendations. The sales accounting information system is the object of research to ascertain how effective and efficient the sales accounting system is for PT. Sagitarius.